MicroRNA-877 inhibits cell proliferation and invasion in non-small cell lung cancer by directly targeting IGF-1R - Zhou, Guohua (Exp Ther Med, 2019)
MicroRNAs (miRNAs/miRs) are frequently differentially expressed in non-small cell lung cancer (NSCLC), and differential miRNAs expression may be closely associated with NSCLC genesis and development. Therefore, an in-depth investigation of the cancer-associated miRNAs that are crucial for NSCLC pathogenesis may provide effective therapeutic targets for patients with this aggressive malignant tumor type. The expression levels and roles of miR-877 have been well studied in hepatocellular carcinoma and renal cell carcinoma. However, the expression pattern and functions of miR-877 in NSCLC as well as associated underlying mechanisms, to the best of our knowledge, have not yet been investigated. The present study revealed that miR-877 expression was downregulated in NSCLC tissues and cell lines. Low miR-877 expression was significantly associated with TNM stage and distant metastasis in patients with NSCLC. Functional experiments demonstrated that recovery of miR-877 expression restricted the proliferation and invasion of NSCLC cells. In addition, bioinformatics analysis predicted insulin-like growth factor 1 receptor (IGF-1R) as a potential target of miR-877. Luciferase reporter assays, reverse transcription-quantitative PCR and western blot analysis further validated that IGF-1R was a direct target of miR-877 in NSCLC. Furthermore, IGF-1R expression was markedly upregulated in NSCLC tissues, and exhibited an inverse correlation with miR-877 expression. Additionally, IGF-1R overexpression reversed the inhibitory effects in NSCLC cells caused by miR-877 upregulation. These findings demonstrated that miR-877 attenuated NSCLC cell proliferation and invasion, at least partly, by downregulating IGF-1R expression, thereby providing an new candidate biomarker for the diagnosis and therapy of patients with NSCLC.